A leader's legacy - Gurley, Gordon ([Stanford, CA] : Stanford Video ; Mill Valley, CA : [Distributed by] Kantola Productions, 2006)
Each one of us has the opportunity to be a leader and a role model. Through our efforts, we can significantly encourage the success and productivity of those around us. But such influence take work. As Jim Kouzes explains, leadership is personal: the people you lead need to know who you are what you care about before they can follow you. In this informative and motivational talk, Jim shares his convictino that we all want to live a life of significance, and that the legacy we leave is the life we lead
Title from title screen
Camera, Damon Meyer, Ron Locey
Keywords: Leadership; Ability